Antibacterial Sensitivity Profile of Bacteria Isolated from Solid Dump Waste of Hetauda Hospital, Nepal - Deo, Satish Kumar; Chaudhary, Sailendra; Yadav, Ajay (Nepal Journal of Health Sciences, 2022)
Introduction: Lack of knowledge and awareness about hospital waste has been a concern amid inadequate hospital waste management facilities and ineffective policies. Objectives: To isolate the bacteria from the waste sample collected from the different departments of the hospital and study the sensitivity profile of the isolated bacteria. Method: Cross-sectional study was conducted for a period of 3 months examining the solid waste of Hetauda hospital of Bagmati Province. Untreated hospital solid waste samples were collected from Hetauda hospital from different departments like general wards, ICU/HDU, Emergency, OPD, Pharmacy, Laboratories. Battery of biochemical were performed according to the guideline of the Bergey’s Manual of Determinative Bacteriology. At the end, sensitivity pattern of the isolates was determined by measuring the zones of inhibition with a calibrated ruler, also interpreted according to Clinical and Laboratory standards institute(CLSI) criteria. Result: A total of 540 bacteria were isolated. Among them higher number of bacteria were isolated from the emergency department and general wards. Both gram positive and negative bacteria isolated from different wards/department has shown a higher percentage of resistant to different antibiotics; Ciprofloxacin, Ceftazidine, Cefotaxime, Gentamycin, Penicilin, piperatazobactum, imipenem, linezolid and cephalexin. Conclusion: Antibiotic resistant to different antibiotic isolated from the hospital has shown greater public health threats. The facilities/waste management in the hospital should be properly handled and regular monitoring should be performed.